The Concept of Internal Quality Assurance in Madrasah Diniyah PP. Al-Hidayah Tanggulangin Sidoarjo - Fiqih, Muhammad; Thaha, Amatillah; Shidiq, Shidiq; Nafis, Moch. Aniq; Martin, Weng (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Background. Madrasah diniyah education develops with the pesantren policy to open up about a systematic and structured formal education system. Purpose. Because of this, madrasah diniyah education also requires a guarantee system which is the focus of the efforts carried out by the internal madrasah itself so that it can be more transformative, inclusive, and open to change in the public interest. Method. The method used is Qualitative with the Field Research model with interviews and direct observation of the research object. This research focuses on the concept of an internal quality assurance system offered to Madrasah Diniyah Education units. Al-Hidayah as an effort to implement SPMI in related education units. Results. The concept offered by the researcher is the eight principles of quality assurance of the International Standard Organization (ISO) version, and the concept of the quality assurance framework version of Umaedi's MPMBS carried out with EDS (School Self-Evaluation), which in the view of researchers can be implemented in the Madrasah Diniyah Education unit PP. Al-Hidayah Conclusion. Internal quality assurance in madrasah Diniyah PP. Al-Hidayah is very doable regarding the ISO version of the quality assurance concept regarding the eight principles of internal quality assurance, Internal quality assurance in madrasah diniyah PP. Al-Hidayah can also be pursued by adjusting the MPMBS concept, namely school-based quality improvement management conceptualized by Umaedi with four frameworks: resources, accountability, curriculum, and school personnel.